Porphyrin π-Stacking in a Heme Protein Scaffold Tunes Gas Ligand Affinity - Weinert, Emily E. (2013)
The role of π-stacking in controlling redox and ligand binding properties of porphyrins has been of interest for many years. The recent discovery of H-NOX domains has provided a model system to investigate the role of porphyrin π-stacking within a heme protein scaffold. Removal of a phenylalanine-porphyrin π-stack dramatically increased O(2), NO, and CO affinities and caused changes in redox potential (~40 mV) without any structural changes. These results suggest that small changes in redox potential affect ligand affinity and that π-stacking may provide a novel route to engineer heme protein properties for new functions.